Does leverage constrain real and AEM around IPO corporate event? evidence from the emerging market - Kalgo, Sani Hussaini; Amin Noordin, Bany Ariffin; Nahar, Hairul Suhaimi (SAGE Publications, 2019)
The article investigates whether Malaysian initial public offering (IPO) firms engage in real and accrual earnings management (AEM) and examines the impact of leverage on the earnings management’s discretionary behaviour of the firms for the period of 2003–2013. The Dechow, Sloan, and Sweeney (1995, The Accounting Review, 70[2], 193–225) cross-sectional modified Jones model was used to estimate discretionary accruals, while Roychowdhury’s (2006, Journal of Accounting and Economics, 42[3]), 335–370) cross-sectional models were used to investigate abnormal real activity discretionary behaviour. The results indicate Malaysian IPO firms engage in real and accrual discretionary behaviour. The graphical presentations of the earnings’ management proxies indicate higher real and AEM for high-leverage firms. Similarly, the multivariate analysis indicates a positive relationship between leverage and earnings management, which is in tandem with the agency cost of free cash flow theory and debt hypothesis. It is also consistent with the pecking-order theory of capital structure. This study suggests that regulatory agencies and standard setters should continue to improve quality of accounting reports in order to protect investors’ invested capital.